BOOK REVIEWS (Journal of Finance, 1978)
Book reviewed in this article: Capital Budgeting Techniques . By F. M. W ilkes . National Monetary Policies and International Financial Markets . By R ichard J. H erring and R ichard C. M arston . By R obert S olomon . The International Monetary System, 1945–1976 . Foreign Direct Investment, Industrialization, and Social Change . By S tephen J ay K orbrin . Revisited Monetary History Revisited. By P. T emin . Bank Holding Companies and the Public Interest . By M ichael A. J essee and S teven A. S eelig . Evolution, Welfare and Time in Economics: Essays in Honor of Nicholas Georgescu‐Roegen . Edited by A nthony M. T ang , F red M. W estfield, and A mes S. W orley . Lectures on the Theory of Production . By L uigi L. P asinetti . Toward Full Employment and Price Stability . By P aul M c C racken, et al .